205 - POSTURE IN MOUTH BREATHING CHILDREN (Fiep Bulletin - online, 2011)
Mouth breathing causes several changes in the individual, from its body position to emotional behavior. According to that standpoint, the aim of this work is to characterize body posture in mouth breathing children aged from 04 to 14 years for both sexes, seeking to differentiate their positions with the cause of mouth breathing and relate them to the complaints mentioned by responsible. Children who participated in the study received an indication for surgical procedures for adenoidectomy, tonsillectomy or adenotonsillectomy for otolaryngologist at Hospital Universitário Infantil Pequeno Anjo (HUPA – Little Angel Infancy University Hospital)in the city of Itajaí (SC). The methodology involved interviews with those responsible to collect information about, seeking behavioral changes during the daily activities. Besides the interviews, one Static Postural Assessment with each child was held, according to Barros Filho (2002); Bienfait (1995) and Santos (2001). To understand and manage the data collected we used the statistics, looking to establish the relationship between postural changes and found oral breathing, the important findings, both related to postural changes, as the daily activities, which could be related to mouth breathing children. The data gathered were explained and discussed with parents or guardians after the Static Postural Assessment based on literature. As a result, we hope to have the production of subsidies for reflection and discussion about the consequences of postural mouth breathing in children, and for the development of educational programs for caregivers and teachers, or physiotherapeutic interventions in rehabilitation nature, contributing to the promotion of health for those children.
Keywords: postural change; child; mouth breath